2005
DOI: 10.1038/sj.gene.6364171
|View full text |Cite
|
Sign up to set email alerts
|

Two genes encoding immune-regulatory molecules (LAG3 and IL7R) confer susceptibility to multiple sclerosis

Abstract: Multiple sclerosis (MS) is a T-cell-mediated disease of the central nervous system, characterized by damage to myelin and axons, resulting in progressive neurological disability. Genes may influence susceptibility to MS, but results of association studies are inconsistent, aside from the identification of HLA class II haplotypes. Whole-genome linkage screens in MS have both confirmed the importance of the HLA region and uncovered non-HLA loci that may harbor susceptibility genes. In this twostage analysis, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 38 publications
3
73
0
2
Order By: Relevance
“…The Alfred patients carrying the T-allele at this locus had significantly higher sIL-7Ra levels compared with patients carrying the A-allele. In prior case-control studies involving Nordic patients, carriers of the T-allele at this locus had an increased risk of multiple sclerosis, 60,61 although replicate studies of multiple sclerosis patients from the United States did not find a similar association. 32 We did not find a relationship between the rs987106 SNP and sIL-7Ra levels in the UARTO patients.…”
Section: Discussionmentioning
confidence: 83%
“…The Alfred patients carrying the T-allele at this locus had significantly higher sIL-7Ra levels compared with patients carrying the A-allele. In prior case-control studies involving Nordic patients, carriers of the T-allele at this locus had an increased risk of multiple sclerosis, 60,61 although replicate studies of multiple sclerosis patients from the United States did not find a similar association. 32 We did not find a relationship between the rs987106 SNP and sIL-7Ra levels in the UARTO patients.…”
Section: Discussionmentioning
confidence: 83%
“…The p.T244I variant, genotyped in this study, has been shown to affect alternative splicing of IL7R exon 6 and alter the amounts of soluble and membranebound protein, thus suggesting a possible mechanism for disease. [6,21] In contrast, no functional outcome has been described for p.I356V, and association studies for this variant (rs3194051) have provided conflicting results, with some studies reporting significant association with risk of MS, [22][23][24] that others could not replicate. [6,25] In summary, our study has confirmed the association between genetic variants in IL2RA and IL7R in MS, and further defined this association to specific disease subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Alleles of the IL7R contribute to MS susceptibility (Zhang et al, 2005;Gregory et al, 2007;Hafler et al, 2007;Lundmark et al, 2007). An Australian case-control study of 63 PPMS, 108 SPMS, 192 RRMS, and 182 healthy controls found that the promoter -504 T allele was overrepresented in PPMS patients (OR ¼ 2.2, p ¼ 0.013) (Booth et al, 2005).…”
Section: Il7rmentioning
confidence: 99%